Islamic Inheritance Law Policies Viewed from The Perspective of Gender Justice according to Applicable Regulations in Indonesia - Salwa Billa Mirza Ridwan (Universitas Muhammadiyah Surakarta, 2024)
As a country where the majority of the population is Muslim, it is possible that many members of the community use the Islamic legal system. But along with the times characterized by progress and technology, the principles of Islamic law continue to progress rapidly and always follow the changing times for the benefit of people in the world. Without distinguishing between men and women. In Indonesian legal literature, the word